# Proof of the derivative of ln(x)

FratBro23
Category:
Mathematics
Price: \$5 USD

Question description

I'm trying to prove that ddxlnx=1x.

Here's what I've got so far:

ddxlnx=limh→0ln(x+h)−ln(x)h=limh→0ln(x+hx)h=limh→0ln(1+hx)h

To simplify the logarithm:

limh→0(1+hx)1h=e1x

^This is the line I have trouble with. I can see that it is true by putting numbers in, but I can't prove it. I know that e1x=limh→0(1+h)1xh, but I can't work out how to get from the above line to that.

limh→0((1+hx)1h)h=ehx

Going back to the derivative:

ddxlnx=limh→0ln(ehx)h=limh→0hxln(e)h=limh→0hx÷h=1x

This proof seems fine, apart from the middle step to get e1x. How could I prove that part?

(Top Tutor) Daniel C.
(997)
School: University of Virginia
Studypool has helped 1,244,100 students

1831 tutors are online

### Related Mathematics questions

Brown University

1271 Tutors

California Institute of Technology

2131 Tutors

Carnegie Mellon University

982 Tutors

Columbia University

1256 Tutors

Dartmouth University

2113 Tutors

Emory University

2279 Tutors

Harvard University

599 Tutors

Massachusetts Institute of Technology

2319 Tutors

New York University

1645 Tutors

Notre Dam University

1911 Tutors

Oklahoma University

2122 Tutors

Pennsylvania State University

932 Tutors

Princeton University

1211 Tutors

Stanford University

983 Tutors

University of California

1282 Tutors

Oxford University

123 Tutors

Yale University

2325 Tutors